Porcine circovirus 2 associated reproductive failure in Indian pigs - SHARMA, RINKU; SAIKUMAR, G (The Indian Journal of Animal Sciences, 2011)
The present study was conducted to find out association of PCV2 infection with reproductive failure and neonatal lnortality in Indian pigs. OUf results indicated that pev 2 infection was associated with pigs showing reproductive failure characterized by smal1 litter size foetal luumnlifications and non-viable neonatal pigs. The diagnosis of pev 2 infection in cases of reproductive failure and neonatal mortality met all 3 essential criteria, viz. typical histopathological findings deITIOnstration of the pev 2 antigen and nucleic acid within the tissues of affected animals. Thus, our results for the first time, established that pev 2 is circulating in the Indian pig population and is causing reproductive failure in gilts and neonatal mortality in piglets. Â